Pengaruh Motivasi Kerja, Keselamatan Dan Kesehatan Kerja (K3) Terhadap Kinerja Karyawan Plant-2 Pada PT. Sinar Agung Pemuda Cikarang - Syafiqki, Ragha Dzaky; Rismayadi, Budi; Pertiwi, Wike (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
Optimizing the performance quality of every organization and/or company has become crucial, necessitating drivers for employees to enhance their performance quality, such as work motivation and occupational health and safety (K3) provided by the organization and/or company to each employee. This study aims to investigate the influence of work motivation and occupational health and safety (K3) on the performance of Plant-2 employees at PT. Sinar Agung Pemuda Cikarang. The research employs a verificative analysis method with a quantitative approach using multiple regression analysis. The results indicate that hypothesis H1 is accepted, signifying that work motivation significantly affects employee performance. Furthermore, H2 is rejected, indicating that occupational health and safety do not significantly affect employee performance. Additionally, H3 is accepted, suggesting a simultaneous influence of work motivation and occupational health and safety on the performance of Plant-2 employees at PT. Sinar Agung Pemuda Cikarang, accounting for 35.7%, with the remaining 64.3% influenced by other variables.